2011
DOI: 10.1038/onc.2011.3
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of novel heat shock protein 90 inhibitor NVP-AUY922 and nilotinib in a random mutagenesis screen

Abstract: To overcome imatinib resistance, more potent ABL tyrosine kinase inhibitors (TKIs), such as nilotinib and dasatinib have been developed, with demonstrable preclinical activity against most imatinib-resistant BCR-ABL kinase domain mutations, with the exception of T315I. However, imatinib-resistant patients already harboring mutations have a higher likelihood of developing further mutations under the selective pressure of potent ABL TKIs. NVP-AUY922 (Novartis) is a novel 4,5-diaryloxazole adenosine triphosphate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…However, inactivation of HSP90 subsequently triggers a heat shock response that may attenuate the anticancer activity of HSP90 inhibitors. AUY922 has been studied to possess enhanced activity in combination with drugs with different targets in a wide spectrum of cancer types . We found that combination of mTOR kinase inhibitor with HSP90 inhibitor displayed synergistic effect against a panel of human breast cancer cells irrespective their ER, HER2 or PI3K status.…”
Section: Discussionmentioning
confidence: 90%
“…However, inactivation of HSP90 subsequently triggers a heat shock response that may attenuate the anticancer activity of HSP90 inhibitors. AUY922 has been studied to possess enhanced activity in combination with drugs with different targets in a wide spectrum of cancer types . We found that combination of mTOR kinase inhibitor with HSP90 inhibitor displayed synergistic effect against a panel of human breast cancer cells irrespective their ER, HER2 or PI3K status.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, combination treatment with Hsp90 inhibitor IPI-504 and imatinib was more effective than either treatment alone in prolonging survival of mice simultaneously bearing both wild-type and T315I leukemic cells (131). Simultaneous exposure of BaF3 cells expressing BCR-ABL mutants including T315I to AUY922 and nilotinib was more effective at reducing the outgrowth of resistant cell clones as well as at survival prolongation of mice transplanted with mixture of BaF3 cells expressing wild-type BCR-ABL and mutant forms (132). Similarly, flavopiridol (semisynthetic flavone and selective inhibitor of CDKs) sensitized imatinibresistant HL/Bcr-Abl cells to GA and it seems that a cocktail of flavopiridol, 17-AAG (or its analogs) and imatinib may be an attractive approach for further investigations (133).…”
Section: Combination Of Hsp90 Inhibitor With Second Therapymentioning
confidence: 99%
“…Once such molecules become more widely available, proteome-wide profiling experiments such as the ones described here should help to define their specificities. HSP90 inhibition is also being considered in the context of combination therapies in order to suppress resistance formation by "oncogene switching" (2,45) or in order to extend the effective treatment time of targeted drugs such as kinase inhibitors (46). Our preliminary data using combinations of geldanamycin and the EGFR inhibitor lapatinib (Fig.…”
Section: Hsp90 Regulated Proteome In Different Cellmentioning
confidence: 99%